Metabolic syndrome in Iran - Berenjy, Shila; Rahmat, Asmah; Hanachi, Parichehr; Lye, Munn Sann; Yassin, Zaitun; Sahebjamee, Farzad (Canadian Center of Science and Education, 2010)
Metabolic Syndrome (MS) also known as syndrome X, the Dysmetabolic Syndrome and Insulin resistance syndrome, refers to a cluster of cardiovascular risk factors including hypertension, glucose intolerance, triglyceridemia and low HDL cholesterol concentrations in blood. This syndrome consists of multiple metabolic risk factors. The significance of MS is that MS and its components seem to be underlying factors for the development of atherosclerotic cardiovascular disease and diabetes type 2. The current article reviews the literature on the prevalence of MS in Iran. According to global statistics, a quarter of the adult population suffers from metabolic syndrome. The prevalence of MS in United States is 24% and 44% of adults over 50 years old suffer from MS. In contrast to this high prevalence of MS in United States of America, its prevalence in some countries such as South Korea is less than 14.2% in men. However, its prevalence in two neighbor country of Iran including Saudi (39.3%) and Turkish (33%) populations is relatively high compared to other countries. We know that 30% of adults in Tehran (Capital city of Iran) suffer from MS and more than 45% of adults older than 20 years old in the Khorasan province (in north east Iran) have MS. This statistics reveal that the prevalence of MS in Iran is even higher than the developed countries and the relation between MS and Coronary Artery disease suggests that we need to continue research on MS, its components, and the association between MS and Coronary Artery Disease.